loT database for non structured data type - LOH, YI LING (2023)
This Final Year Project (FYP) delves into the development and evaluation of FastTextProcessor, a Python library designed to simplify two fundamental data processing tasks: querying by string and calculating mean values. It deftly addresses the first objective by offering a data querying mechanism that liberates users from the hassles of populating data like existing NoSQL databases. With FastTextProcessor, users can query data directly from the file directory, accelerate the data extraction process. Next, the second objective finds its fulfillment in FastTextProcessor's innate ability to query the data and perform calculation directly from the file directory without the need of formatting data like conventional databases or other data extraction tools. In a world where time is money, FastTextProcessor's capacity to expedite coding workflows underscores its importance. In summary, FastTextProcessor stands as a beacon of innovation in the realm of data extraction. It aligns seamlessly with the project's objectives, enabling data to be queried directly and processed without the burden of extensive formatting. Its potential to streamline data analytics workflows is bound to empower users and revolutionize their approach to data analysis